Does M-shaped curve still exist?: Revealing vivid career trajectory of well-educated women in South Korea - JIYEA PARK (Adult Education Research Conference, 2024)
The purpose of this study was to reveal how well-educated Korean women face the M-shaped curve in the Korean job market in their mid-20s to late 30s.
Keywords: Korean Millennial women; Overqualified; Career trajectory; M-shaped curve